Epilepsia lesional de origen cerebeloso - Bartuluchi, Marcelo; Liñares, Juan; Ruiz Johnson, Agustín; Mantese, Beatriz; Lubieniecki, Fabiana; Stefanoff, Nadia; Reyes, Gabriela; Caraballo, Roberto (Revista Argentina de Neurocirugía, 2020)
The subcortical origin of epilepsy has been a subject of debate and only the subcortical structures were given a role in the distribution, modulation and alteration of cortical activity. However, neurophysiological and neuroimaging studies of recent decades have provided enough information to confirm the onset of some epileptic seizures in subcortical structures. We present 4 pediatric patients with cerebellar lesions and refractory epilepsy, we reviewed the literature, analyzed the forms of presentation, the neurophysiological findings and long-term results with surgery.
Keywords: cerebellar epilepsy; epilepsy surgery; hemifacial spasms; cerebellar tumor